Biophysical insight reveals tannic acid as amyloid inducer and conformation transformer from amorphous to amyloid aggregates in Concanavalin A (ConA). Issue 5 (4th April 2018) - Khan, Mohsin Vahid; Ishtikhar, Mohd.; Siddiqui, Mohammad Khursheed; Zaman, Masihuz; Chandel, Tajalli Ilm; Majid, Nabeela; Ajmal, Mohd. Rehan; Abdelhameed, Ali Saber; Shahein, Yasser E.; Khan, Rizwan Hasan
Abstract : The aggregation phenomenon (amyloid and amorphous) is associated with several pathological complications in human, such as Alzheimer's, Parkinson's, Huntington, Cataract diseases, and Diabetes mellitus type 2. In the present study we are offering evidence and breaking the general belief with regard to the polyphenols action as protein aggregate inhibitors. Herein we confirm that tannic acid (TA) is not only an amyloid inducer, but also it switches one type of conformation, ultimately morphology, into another. We ascertain based on our findings that aggregates are not rigid structures and the stability can be challenged under certain conditions. This study also confirms that unfolded and amorphous aggregates can serve as precursors of amyloids and TA interactions with unordered aggregates (amorphous) bringing orderliness in the conformation via amyloidosis. The shifting of unordered conformation toward orderliness is governed by the modulation in surface hydrophobic patches in Concanavalin A (ConA). Hence, a degree of exposed hydrophobic cluster can be claimed as a strong parameter to detect and distinguish the native, amorphous and both types of amyloids. Turbidity and Rayleigh light scattering measurements followed similar pattern while Thioflavin T and 1-anilino-8-naphthalene sulfonate fluorescence assays of the binding with amorphous and amyloid followed an inverse relation. Electron microscopic studies revealed the morphological variation in the ConA at 65°C as amorphous while the ConA treated with TA followed by heat treatment at 65°C was defined as amyloid in nature. Interestingly for the first time we are reporting the slight agglutination activity by the ConA amyloids.